NURSES’ EXPERIENCES IN PROVIDING SPIRITUAL CARE OF PATIENTS WITH HEART FAILURE - Okviasanti, Fanni; Ilmy Muhalla, Hafna; Harianto, Susilo; Rahmadi Purwanto, Cucuk; Yusuf, Ah; Dian Kurniawati, Ninuk; Lin, Mei-Feng (Journal of Vocational Nursing, 2025)
Introduction: Spirituality plays an important role in the physical health of patients with chronic diseases. This study aimed to explore the experiences of nurses in providing spiritual care to patients with heart failure (HF) in Indonesia. Method: This study employed a descriptive exploratory design with a qualitative approach. Thirteen nurses from the cardiology unit were selected using purposive sampling. Data were collected through semi-structured interviews and field notes. Thematic analysis was conducted to analyze the data. Results: Five major themes emerged, including perceptions regarding spiritual care, the importance of meeting the spiritual needs of patients, implementation of spiritual care, obstacles in providing spiritual care, and nurses’ hopes. Most participants associated spiritual care with religious practices. All participants believed that the spiritual needs of patients with HF must be met. However, spiritual care was still rarely implemented. Nurses commonly assisted patients in performing religious practices rather than addressing existential needs. The barriers to providing spiritual care originated from patients, nurses, and the availability of tools. The nurses hoped that specific personnel could provide spiritual care and that spiritual guidance activities in the hospital could be reactivated. Conclusions: Spiritual care remains a neglected aspect in the treatment of patients with HF. Facilitating religious practices is the primary intervention that fulfills the spiritual needs of patients with HF in Indonesia.